ANALISIS PENERAPAN TOTAL QUALITY MANAJEMEN (TQM) PADA PERUSAHAAN BANGUNAN LEPAS PANTAI PT. APEXINDO PRATAMA DUTA - Jalil, Jalil (Riset Sains dan Teknologi Kelautan, 2022)
TQM or Total Quality Management is a quality management system that focuses on customers by involving all levels of employees to carry out continuous improvement or improvement. Another definition, Total Quality Management is a management strategy that aims to instill quality awareness in all processes within an organization or company. Steps to implement TQM in a construction project or company: Obtain client commitment to quality, raise awareness, educate, and change staff attitudes, develop a process approach to TQM, prepare quality project plans for all levels of work, exist continuous improvement institutions, promote staff participation and control contributions using quality circles and program motivation, and reviewing quality plans and measuring performance. 2020 was a year of change for Apexindo, as estimated utilization of our services was substantially impacted by reduced activity from oil companies. This creates very challenging business conditions, while it is necessary to maintain existing assets as many projects are canceled or postponed. Implementation of TQM in the PT company. Apexindo (Oil Drilling) has been very good, seeing that Apexindo's consistent performance over several decades has generated trust and recognition from consumers. This is proven by the many awards the Company has received. Apexindo succeeded in renewing its three certifications, namely ISO 9001:2008 in Quality Management Systems, ISO 14001:2004 in Environmental Management Systems, and OHSAS 18001:2007 in Safety and Health Management Systems.